Biotype characterization and genetic diversity of the greenbug, Schizaphis graminum (Hemiptera: Aphididae), in north Tunisia - KHARRAT, IMEN; BOUKTILA, DHIA; MEZGHANI-KHEMAKHEM, MAHA; MAKNI, HANEM; MAKNI, MOHAMED (Revista Colombiana de Entomología, 2012)
The greenbug Schizaphis graminum, is a major pest of wheat worldwide. Biotype screening of this pest is essential to develop pest management programs. In this research, eight greenbug clones, collected on wheat in the cereal-growing region of Béja (north Tunisia), were used to determine their damage on six reference wheat cultivars. All tested clones shared a unique biotypic profile, similar to biotype C. Moreover, DNA from the tested clones and that from seven reference clones of biotypes C, E, F, G, H, I and K, was analyzed, using 5 RAPD-PCR primers. The UPGMA method clustered samples into two distinct clades: a first one (I) included clones from north Tunisia, which were clearly associated to agricultural biotypes C, E, I and K, while a second clade (II) included non agricultural biotypes F, G and H. Results reported in this paper suggest that resistance genes Gb2, Gb3, Gb4, Gb5 and Gb6 in wheat would be the most efficient if used in wheat improvement programs for resistance against greenbug in Tunisia.